Prenatal Stimulation Program: Basis for the Motor Development of Neonates at Essalud Hospital in Tarapoto, 2021. - Cardenas-Macedo, Gissela Giovanna (2023)
Introduction: Prenatal stimulation is a technique that uses a series of stimuli such as sound (the mother's voice and music), movements, pressures, vibrations, and lights to communicate with the unborn baby. This helps the child learn to recognize and respond to various situations, promoting their sensory, physical, and mental development. Therefore, the present article focuses on the development of prenatal stimulation. Objective: To determine if the Prenatal Stimulation Program significantly influences the Motor Development of neonates at Essalud Hospital Tarapoto in 2021. Materials and Methods: This study was experimental and focused on studying causal relationships using experimental methodology to control phenomena. It employed a quasi-experimental design, where the subjects included in the study groups were already assigned or constituted. Once the two groups were established, both were evaluated in terms of the dependent variable. Then, one of the groups received the experimental treatment, while the other continued with routine tasks or activities (García, 2010). The study sample consisted of two groups: M1 = 25 neonates, a sample without the Prenatal Stimulation Program for their mothers, and M2 = 25 neonates, a sample with the Prenatal Stimulation Program for their mothers. The survey and experimentation techniques were used, with the questionnaire and the Peruvian Test of Psychomotor Development being the applied instruments. Results: By applying the T-Student test for difference of proportions with a 95% confidence level, it was concluded that the Prenatal Stimulation Program significantly influences the Motor Development of neonates at Essalud Hospital Tarapoto. It is worth mentioning that the proportions of neonates with "developmental disorders" were used for both samples, allowing us to observe if the proportion of babies in M2 was lower than in M1 on that measurement scale. Conclusions: The Prenatal Stimulation Program significantly influences the Motor Development of neonates at Essalud Hospital Tarapoto with a 95% confidence level.